How to hold someone in your heart : a novel - Tsujimura, Mizuki, 1980- (Scribner, 2026)
Ayumi has a rare and mysterious ability, inherited from his grandmother. During a full moon and guided by strict rules, he arranges meetings between souls who have passed and those they left behind. However, after years in this role, Ayumi begins to question its meaning and the impact it has had on his life. As he juggles his supernatural calling with his full-time job as a toy designer in Tokyo, Ayumi quietly wonders if he will ever find the peace he so often helps others attain. Meanwhile, he assists five individuals, including: a rising film star who seeks closure with the father who abandoned him; a passionate amateur historian longing to meet a forgotten sixteenth-century warlord; and a former cook whose repeated requests to visit an upper-class woman in the afterlife have been denied-but who refuses to give up on love.